2014
DOI: 10.15252/embj.201488142
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs at the interface of cellular stress and disease

Abstract: microRNAs (miRNAs) are a family of small, non-coding RNAs, which provides broad silencing activity of mRNA targets in a sequencedependent fashion. This review explores the hypothesis that the miRNA machinery is intimately linked with the cellular stress pathway and apparatus. Stress signaling potentially alters the function of the miRNA-bioprocessing core components and decompensates regulation. In addition, dysregulation of miRNA activity renders the cell more prone to stress and emerges as a new pathway for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 138 publications
4
85
1
Order By: Relevance
“…This response is sometimes mediated by miRNA function through regulating the amount of miRNAs, the amount of mRNA targets, or the interaction of miRNA-protein complexes. Thus, clarifying miRNA-mediated regulatory networks would provide a novel insight into the genetic improvement of species stress tolerance [18,19]. Herein, we found that the role of miR-204 in hypoxia tolerance in tilapia.…”
Section: Discussionmentioning
confidence: 89%
“…This response is sometimes mediated by miRNA function through regulating the amount of miRNAs, the amount of mRNA targets, or the interaction of miRNA-protein complexes. Thus, clarifying miRNA-mediated regulatory networks would provide a novel insight into the genetic improvement of species stress tolerance [18,19]. Herein, we found that the role of miR-204 in hypoxia tolerance in tilapia.…”
Section: Discussionmentioning
confidence: 89%
“…A peripheral blood compartment that may be particularly relevant are the exosomes, cellular miRNAs-containing secretory vesicles able to attach recipient cells and release miRNAs potentially modulating their function [127]. Recent results clearly indicate that miRNAs are important mediators of stress responses and their deregulation has been implicated in a variety of stress-related neuropathological conditions [128,129]. Accordingly, UPR regulates the expression of many miRNAs that play an important role in the regulation of life and death decisions during ER stress [130].…”
Section: Intercellular Communication Mediated By Micrornasmentioning
confidence: 99%
“…miRNAS regulate mRNA expression by either inducing mRNA degradation or translational repression (Emde & Hornstein, 2014;SmithVikos & Slack, 2012). First discovered in C. elegans, miRNAs have become another important set of molecular regulators, as their appropriate or aberrant function has been implicated in the regulation of stem cell selfrenewal, cell proliferation, stress response, metabolism, apoptosis, among others cellular processes (Abe & Bonini, 2012;Emde & Hornstein, 2014;Jung & Suh, 2012). Hence, it is not surprising that extensive research has identified aberrant mRNA regulation in neurodegeneration and aging (Abe & Bonini, 2012;Szafranski, Abraham, & Mekhail, 2015).…”
Section: Mirnas In Longevity Health and Diseasementioning
confidence: 99%